Using design of experiments to improve precision glass moulding. (1st January 2013) - Gleason, Benn; Wachtel, Peter; Musgraves, J. David; Richardson, Kathleen
A design of experiments (DOE) approach was used to characterise the effect of process parameters, including heating and cooling rates, soaking times, moulding viscosities, and forces applied during the moulding and cooling stages on the repeatability of the final thickness of moulded N-BK7 and LBAL35 glasses using a precision glass moulding (PGM) machine. Analysis of the DOE showed that process parameters that lengthen the overall time of the moulding process tend toward more repeatable final thicknesses. Using the ideal parameters found by the DOE, the error in the final thickness was held within ±0.05 mm.